PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA APOTEK SEKATA DI KARAWACI KOTA TANGERANG SELATAN - Alpianto, Ferdi; Mustakim, Masran (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to find out whether there is an effect of product quality and price either partially or simultaneously on Customer Satisfaction on karawaci pharmacy sekata. This type of research uses an associative quantitative approach in collecting the sample using the Simple random sampling technique. This research was conducted on consumers who had made purchases at pharmacy sekata. The sampling technique used the slovin formula and obtained a sample of 98 respondents. Based on the partial results of the study (t test) it was concluded that product quality has a significant effect on Customer Satisfaction by obtaining t count > t table or (4.305 > 1.984). While partially the price has a significant effect on purchasing decisions with the obtained value of t count > t table or (4.439 > 1.984). Based on the simultaneous regression test (F test) the product quality variables (X1) and price (X2) have a significant effect on Customer Satisfaction (Y) by obtaining F count > F table or (76,557 > 2,310), this is also reinforced by ρ alue < Sig. 0.050 or (0.000 < 0.050).